1987
DOI: 10.1111/j.1600-0714.1987.tb00680.x
|View full text |Cite
|
Sign up to set email alerts
|

Two cystic lesions with features of both the botryoid odontogenic cyst and the central mucoepidermoid tumour: sialo‐odontogenic cyst?

Abstract: Two cases are reported with identical clinical, radiographical and histological features. These features share a combination of the botryoid odontogenic cyst and a central mucoepidermoid tumour, and it is suggested that the term sialo‐odontogenic cyst be adopted for such lesions to avoid confusion and mismanagement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
79
2
3

Year Published

1992
1992
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(91 citation statements)
references
References 11 publications
1
79
2
3
Order By: Relevance
“…Many of these have been single case reports; however, several short series and detailed reviews of the literature have also been published [1,2,6,7,11,[13][14][15][16][17][18][19][20][21][22][23][24][25][26]. Therefore, the GOC, though rare, is now relatively well known, especially among oral and head and neck pathologists.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many of these have been single case reports; however, several short series and detailed reviews of the literature have also been published [1,2,6,7,11,[13][14][15][16][17][18][19][20][21][22][23][24][25][26]. Therefore, the GOC, though rare, is now relatively well known, especially among oral and head and neck pathologists.…”
Section: Discussionmentioning
confidence: 99%
“…In 1987, Padayachee and van Wyk [1] published two cases of unusual odontogenic cysts, which possessed features of botryoid odontogenic cyst and central mucoepidermoid carcinoma, and proposed the term ''sialo-odontogenic cyst'' for these lesions. In 1988, Gardner and colleagues [2] described eight additional cases, preferring the term ''glandular odontogenic cyst'' (GOC).…”
Section: Introductionmentioning
confidence: 99%
“…Padayachee and Van Wyk [1] presented multilocular cystic lesions that were similar to botryoid odontogenic cysts but with a glandular ingredient and suggested the name ''sialo odontogenic cyst''. In 1988, Gardner et al [2] reported eight other cases and called the lesions glandular odontogenic cysts (GOCs) because there was a mucin structure in the cyst epithelium that had no finding of salivary gland origin.…”
Section: Introductionmentioning
confidence: 99%
“…Glandular Odontogenic Cyst (GOC) is relatively a rare entity, that was first described by Padayachee and Van Wyk [1] in 1987 under the term 'sialo-odontogenic cyst' attributing its possible etiology to salivary glands. The term 'Glandular odontogenic cyst' (GOC) was first coined by Gardner et al [2], in 1988 as an odontogenic origin.…”
Section: Introductionmentioning
confidence: 99%
“…GOC has gained special attention by clinicians and pathologists due primarily to two reasons. First, is the histomorphologic features between GOC, Lateral Periodontal Cyst (LPC), Botroid Odontogenic Cyst (BOC), and Central Mucoepidermoid Carcinoma (CMEC) of the jaws [1,4,5,6] second, is the potential aggressive behaviour of the lesion. Radiographically, GOC does not display specific or pathognomonic features.…”
Section: Introductionmentioning
confidence: 99%